Can The Spectra Of Hermitian Operator Be Invariant Under x ?? p ? :Case Study :1D General Oscillator - Rath, Biswanath (JOURNAL OF ADVANCES IN PHYSICS, 2018)
We address an intriguing question on spectral invariance in quantum mechanics on exchange of co-ordinate and momentum X<– –> p considering general oscillator as an example.